CITY BRANDING DESIGN OF BUKITTINGGI CITY AS THE CITY IDENTITY OF “HISTORICAL CITY” - Pratama, Wendo Afriyoma; Asril; Minawati, Rosta (Antis-Publisher, 2024)
Objective: This study aims to develop an effective city branding strategy for Bukittinggi City, focusing on the creation of a visual identity that encapsulates the city’s historical significance and attractions. Method: The research employs the Glas Box method, as developed by Sarwono and Lubis, involving stages of observation, field interviews, literature review, concept design, and iterative evaluation to refine the branding output. The primary focus is on designing a tourism logo and a web design that visually represent Bukittinggi’s unique cultural and historical landmarks. Results: The study produces a comprehensive city branding identity, with a tourism logo and web design that effectively communicate Bukittinggi's appeal to domestic tourists, particularly those from outside the city. Novelty: This research offers a novel approach to city branding by integrating local history into a visually compelling and functional identity, tailored for the tourism sector. The outcome is presented through a work exhibition titled